Comprehensive genome and transcriptome analysis of the dermatophyte Trichophyton schoenleinii reveals the candidate pathogenic genes. Issue 6 (11th March 2021) - Ge, Li‐Yu; Liu, Jia; Zheng, Hai‐Lin; Mei, Huan; Liang, Guan‐Zhao; Liu, Wei‐Da
Abstract: Background: Trichophyton schoenleinii is an anthropophilic dermatophyte that causes tinea favosa. Nowadays, it remains an important pathogen in some regions of the world, mainly epidemic in Africa and West Asia. Despite the medical importance of T. schoenleinii infections, a high‐quality reference genome for T. schoenleinii is still unavailable, neither its transcriptomic profile. Objectives: The aim of the current study was to improve understanding of the underlying pathogenic mechanism of T. schoenleinii, and to define the candidate pathogenic genes of T. schoenleinii . Methods: Comprehensive genomic analysis of T. schoenleinii was carried out by Illumina and PacBio sequencing platforms. Transcriptome profiles of T. schoenleinii cultured in vitro in two media containing either keratin or soy protein were determined using RNA sequencing (RNA‐seq) technology. Results: Here, we present the first draft genome sequence of T. schoenleinii strain T2s, which consists of 11 scaffolds containing 7474 predicted genes. Transcriptome analysis showed that genes involved in keratin hydrolysis have higher expression in T. schoenleinii grown in keratin medium, including genes encoding proteases, cysteine dioxygenase and acetamidase. Other genes with higher expression include genes encoding the components of the pH‐responsive signal transduction pathways and transcription factors, many of which may play a role in pathogenicity. Conclusion: In summary, this study provides new insights into the pathogenic mechanism of T. schoenleinii and highlights candidate genes for further development of novel targets in disease diagnosis and treatment of tinea favosa.